Effectiveness of Jengkol (Pithecollobium Lobatum) Fruit Peel as A Botanical Repellent for Munia Birds (Lonchura Spp.) in Bogor, West Java, Indonesia (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Three munia birds, javan munia (Lonchura leucogastroides), white-headed munia (Lonchura maja), and scaly-breasted munia (Lonchura punctulata), are important pests at rice fields in Indonesia. These seed-eating birds can consume up to 10% of their body weight in seeds, causing significant damage. Botanical repellents, which use active ingredients derived from plants, are an eco-friendly method to deter pests. This study examined the potential of jengkol (Pithecollobium lobatum) fruit peel as a natural repellent to control munia birds in the rice fields. The research was conducted in Cicadas Village, Ciampea District and Situ Gede Village, West Bogor District. Repellent concentrations of 0, 400, 600, and 800 g jengkol fruit peel per liter water, then it diluted within water with 10 ml of jengkol fruit peel concentrate per liter water. Each concentration were applied to 75 m² plots within spray volume of 3.75 liter. Bird populations were observed over seven consecutive days. The results showed that no concentration approached the 70% repellent standard, with the effect lasting only one day after spraying due to various factors including rain, heat, and the surrounding environment. These findings suggest that the jengkol fruit peel for bird repellent is ineffective in its current form, therefore it need a sticker. Keywords : Efficacy, important pest, seed-eating birds